The self-reported perceptions of the multi-disciplinary team regarding standards of neurodevelopmental supportive care in the neonatal intensive care unit - Butler, Meghan Leanne (My University, 2018)
Premature infant mortality and poor neurodevelopmental outcomes are great concerns worldwide as well as in South African Neonatal Intensive Care Units (NICUs). The Neurodevelopmental Supportive Care (NDSC) approach focuses on the improvement of neurodevelopmental outcomes by promoting a uterinelike environment by limiting noxious stimuli provided by the NICU environment. It is evident that developmental outcomes in the NICU need to be optimised and this can occur through further education and training of the multi-disciplinary team (MDT) on the application of NDSC guidelines in these units. In order to develop and implement such a programme, it is vital to first determine the perceptions of the MDT on the current standards of NDSC before a training programme can be developed and implemented. The aim of this study was to determine the self-reported perceptions of the MDT regarding the current standards of developmental care in two public-sector NICUs in Gauteng. A quantitative, cross sectional survey design was used to describe the selfreported perceptions of the MDT (qualified specialists, doctors, nurses and all therapists) working in the NICUs. Data was collected by making use of an existing checklist, the Instrument for Neurodevelopmental Supportive Care. The quantitative data gained from the questionnaire was studied manually, ultimately portraying a great deal of optimal as well as high-risk practices. The prevalence of high-risk practices for both hospitals was found to be evidently higher compared to the optimally applied elements. It included the categories of NICU design, family-centred philosophy, environmental stimulation, pain management, knowledge of preterm infant development as well as feeding. Very few significant differences were identified between the two participating hospitals, thus making it apparent that the participating MDT members perceive that a lot of room for improvement is present regarding the application of NDSC in the NICUs of the two participating hospitals. Key words: South Africa, NICU, Neurodevelopmental Supportive Care, developmental care, preterm infant, Multi-disciplinary team
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy Johannesburg June 2018.
Keywords: Neurodevelopmental Supportive Care; Intensive Care Units, Neonatal